Out of Shape During Stress: A Key Role for Auxin. (September 2018) - Korver, Ruud A.; Koevoets, Iko T.; Testerink, Christa
Abstract : In most abiotic stress conditions, including salinity and water deficit, the developmental plasticity of the plant root is regulated by the phytohormone auxin. Changes in auxin concentration are often attributed to changes in shoot-derived long-distance auxin flow. However, recent evidence suggests important contributions by short-distance auxin transport from local storage and local auxin biosynthesis, conjugation, and oxidation during abiotic stress. We discuss here current knowledge on long-distance auxin transport in stress responses, and subsequently debate how short-distance auxin transport and indole-3-acetic acid (IAA) metabolism play a role in influencing eventual auxin accumulation and signaling patterns. Our analysis stresses the importance of considering all these components together and highlights the use of mathematical modeling for predictions of plant physiological responses. Highlights: Recent findings in active auxin transport over organelle membranes and the influence of apoplastic and cytosolic pH on passive auxin flow into the cell highlight the importance of short-distance auxin transport for local auxin maxima in roots exposed to stress. Based on previously published gene expression data, we have identified stress-induced expression patterns of IAA biosynthesis and conjugation genes in the root that could be relevant for IAA accumulation patterns. These results underscore the importance of incorporating IAA homeostasis into models predicting auxin levels and flow. Recent advances in mathematical models involving auxin-related processes highlight the value of combining in planta and in silico experiments when unraveling complex hormonal changes in plants.